DEVELOPMENT AND VALIDATION OF STABILITY-INDICATING REVERSE-PHASE HIGHPERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR THE SIMULTANEOUS QUANTIFICATION OF POTENTIAL DEGRADATION PRODUCTS OF REGADENOSON FROM ITS PARENTERAL DOSAGE FORM - Zope, Murlidhar V; Patel, Rahul M; Patel, Ashwinikumari; Patel, Samir G (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective was to develop and validate the stability indicating reverse-phase high-performance liquid chromatography method for the quantification of potential degradation products of regadenoson (REGA) from its injectable dosage form. Methods: YMC-PAK ODS AQ, 150 mm × 4.6 mm, 3 μm composed with hydrophobic high carbon loading and a relatively hydrophilic surface chemically bonded to porous silica particles column was used with the temperature maintained at 40°C. Mobile phase A composed of 0.1% triethylamine buffer having pH 4.5 while mobile phase B is 100 % acetonitrile was used for gradient elution with 1.5 ml/min as a flow rate. The wavelength used for quantification was 245 nm and 20 μl as an injection volume. The suitability of the method has been checked and validated according to the International Council for Harmonization (ICH) guidelines for different parameters, namely, specificity, linearity, accuracy, precision, limit of quantification (LOQ), Limit of detection (LOQ), and robustness studies. Results: The resolution between REGA and its two-degradation product is >8.0 for all pairs of components. The high correlation coefficient (r2>0.990) values are for drug and all potential degradation products from LOQ to 150% of specification limits for impurities calculated based on the maximum daily dose of REGA. LOQ for the drug as well as each degradation product is <0.02% w/w. The % relative standard deviation (RSD) for precision and intermediate precision is in the range of 0.17–0.89, and % RSD for precision at LOQ is 0.86–2.35. The % RSD for robustness study is maximum 2.59. Conclusion: The developed method can quantify the specified and unknown degradation products from 0.1% in the injectable dosage form which indicates that method is sensitive. Method fulfills the ICH criteria for its different validation parameters and demonstrates that the developed analytical method is highly specific, precise, and robust and would have a great value when applied in quality control and stability studies for REGA injection.